A new species of Apterichtus (Anguilliformes: Ophichthidae) from the Marquesas Islands - Hibino, Yusuke; Mccosker, John E.; Kimura, Seishi (Zootaxa, 2016)
A new finless ophichthid eel, Apterichtus succinus sp. nov., is described based on a single specimen collected from the Marquesas Islands. The new species closely resembles A. klazingai Weber, 1913 in the shape and coloration of its head and its total vertebral count. The former differs from the latter in having more preopercular pores (4 vs. 3), fewer preanal vertebrae (54 vs. 56–63), a single tooth on the prevomer (generally absent), a shorter head (14.8 in TL vs. 12–14 in TL), and larger spots on its head and nape. Three species of Apterichtus (A. succinus, A. klazingai, and Apterichtus mysi McCosker & Hibino, 2015) are recognized from the Marquesas Islands.